Effects of organizationally endorsed coaching on performance and validity of situational judgment tests - STEMIG, Melissa S. (Institutional Knowledge at Singapore Management University, 2015)
There is growing interest in organizationally provided or organizationally endorsed coaching. However, little is known about the effects of such coaching on test scores in operational settings. This study reports on an examination of such a program in the context of the use of a situational judgment test (SJT) for medical school admissions. We examine the effects of multiple types of coaching methods on SJT scores and on their construct-related and predictive validities. Results suggest that (1) commercial coaching techniques may not be as effective as previously thought, whereas organizationally provided methods may be more effective, and that (2) the criterion-related validity of the SJT scores is not degraded by the availability of coaching. Generally, this study illustrates that concerns about potential unfairness of coaching can be countered by making effective coaching available to all examinees, in the form of organizationally endorsed coaching.